Corporate Social Responsibility and Tax Aggressiveness: Evidence from Indonesia - Fredi Kristiadi; Elisabeth Penti Kurniawati; Ahmad Maulin Naufa (Universitas Airlangga, 2020)
The purpose of this research is to examine the impact of tax aggressiveness on corporate social responsibility (CSR) and its reversal. It also finds out which one of those relationships with more considerable influence. The population of this research is manufacture companies listed on the Indonesian Stock Exchange over the period 2008-2019. This research used a purposive sampling method and found 67 companies. We test the multiple regressions using the generalized method of moments (GMM) to analyze the hypotheses. The results depict that CSR does not affect tax aggressiveness. However, tax aggressiveness has a significant effect to enhance CSR. Therefore, the relationship between CSR and tax aggressiveness is only one direction.